2018
DOI: 10.1001/jama.2018.5623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of More vs Less Frequent Follow-up Testing on Overall and Colorectal Cancer–Specific Mortality in Patients With Stage II or III Colorectal Cancer

Abstract: clinicaltrials.gov Identifier: NCT00225641.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(174 citation statements)
references
References 23 publications
9
153
0
3
Order By: Relevance
“…Studies in colorectal cancer suggest that more frequent specialised follow-up care, including more diagnostic investigations, have no effect on CR detection or survival (Snyder et al, 2018;Wille-Jørgensen et al, 2018). This indicates that improvements in the detection of CR should be based on increased focus on symptomatic presentation.…”
Section: Interpretation and Implicationsmentioning
confidence: 99%
“…Studies in colorectal cancer suggest that more frequent specialised follow-up care, including more diagnostic investigations, have no effect on CR detection or survival (Snyder et al, 2018;Wille-Jørgensen et al, 2018). This indicates that improvements in the detection of CR should be based on increased focus on symptomatic presentation.…”
Section: Interpretation and Implicationsmentioning
confidence: 99%
“…Stage IV renal adenocarcinoma presents an extremely low five-year survival rate of 0-10% [1], while the recurrence rate may be as high as 23% [2]. While the recurrence rate of colorectal carcinoma is similar to that of renal adenocarcinoma at 19.4% to 21.6%, the five-year survival rate is significantly higher at 88.6% to 89.4% [3]. Pancreatic ductal adenocarcinoma has an extremely low survival rate of 10% to 28% [4] after one year due to a very high recurrence rate of 65.5% [5].…”
Section: Introductionmentioning
confidence: 96%
“…In this single-institution retrospective analysis we found marked rates antigen levels at high-frequency or low-frequency intervals. 16 The authors reported no significant difference in either 5-year overall mortality or colorectal cancer-specific mortality between groups. A retrospective study conducted by the Alliance for Clinical Trials in Oncology Cancer Surveillance Optimization Working Group reinforced these findings with data from the National Cancer Data Base demonstrating no significant association between the intensity of surveillance and detection of recurrent disease for patients with stage I, II, or III colorectal cancer.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, other literature challenges the assumption that increased postoperative surveillance necessarily portends better clinical outcomes. A recently published randomized clinical trial assigned patients with stage II or III colorectal cancer to cohorts that mandated computed tomography imaging and carcinoembryonic antigen levels at high‐frequency or low‐frequency intervals . The authors reported no significant difference in either 5‐year overall mortality or colorectal cancer‐specific mortality between groups.…”
Section: Discussionmentioning
confidence: 99%